Ir(tri-N-heterocyclic carbene)-catalyzed upgrading of glycerol: C-C bond formation for the synthesis of α-hydroxy acids - Byeon, Heemin; Kim, Jaeho; Lee, Mi Hyun; Jang, Hye Young (Organic and Biomolecular Chemistry, 2024)
Ir(triNHC) complexes catalyzed glycerol and alcohol dehydrogenative coupling, yielding diverse α-hydroxy acids. Unlike conventional conditions, Ir(triNHC) facilitated additional C-C bond formation after lactic acid production from glycerol, exhibiting high TOFs. This protocol successfully converted 1,2-propanediol and sorbitol into α-hydroxy acids, highlighting biomass-derived sources’ potential as valuable platform chemicals.
Keywords: C-C bond formation; Condition; Dehydrogenative coupling; Hydroxy acids; Lactic acid production; N-heterocyclic carbenes; Platform chemicals; Propanediols; Source potentials